The Effects of Drilling Technique on the EFL Students’ Ability in Answering the Reading Section of TOEFL Test - Atmayurid Mansyur; Syarifuddin Dollah; Andi Muliati (Universitas Muhammadiyah Enrekang, 2023)
For students majoring in English Education at IAIN Parepare in the 2019–2020 academic year, the goal of this study is to ascertain whether or not the application of drilling techniques in reading might enhance reading scores on the TOEFL test. A quasi-experimental design was used in this investigation. In the 2019–2020 academic year, English Education majors at IAIN Parepare made up the study's population. A total of 70 students were involved in the study, divided into two sample groups of 35 students each for the experimental group and the control group